DEFINITION AND GRAMMATICAL STRUCTURE IN THE FORMATION OF LABOR-RELATED PROVERBS IN ENGLISH AND UZBEK LANGUAGES (SCIENCE TIME JOURNAL, 2026)
This article analyzes the grammatical structure of labor-related proverbs in the English and Uzbek languages. In the course of the research, the grammatical structures of proverbs in both languages, as well as their similarities and differences, were identified. The study is devoted to a comparative analysis of the grammatical structure of labor-related proverbs in English and Uzbek. The work scientifically examines the syntactic structure of proverbs specific to both languages, types of sentences, grammatical forms, and their semantic load. During the research, it was observed that English proverbs predominantly employ simple and concise sentence constructions, imperative forms, and generalized subjects. In contrast, Uzbek proverbs demonstrate a wider use of complex sentences, parallelism, ellipsis, and grammatically rich morphological means. Furthermore, it is substantiated that the grammatical structure of proverbs plays an important role in realizing their educational and didactic functions. The results of the study make it possible to identify common and distinctive features in the  paremiological systems of the two languages, as well as to gain a deeper understanding of their linguocultural characteristics.